Successful treatment of bilateral empyema with bilateral fistulae using free intercostal muscle flap - Junko Okamura; Naohiro Kobayashi; Takahiro Yanagihara; Shinji Kikuchi; Yukinobu Goto; Yukio Sato (Surgical Case Reports, 2021)
Abstract Background Bilateral empyema is rare and can be life-threatening. Few cases have ever been reported about bilateral empyema with fistula on both sides. We herein report a case of bilateral empyema with bilateral fistulae that was treated with a 2-stage operation. Case presentation The patient was a 40 year-old man with uncontrolled diabetes mellitus, severe emaciation and remarkably decayed teeth. On his admission, computed tomography showed bilateral pneumothorax and pleural effusion. Thoracentesis revealed a cream-colored purulent pleural effusion from both sides of the pleural cavity. Bilateral empyema with fistulae on both sides due to a ruptured lung abscess was diagnosed. 7 days after his administration, we performed the first surgery. There were 3 fistulae in the right lateral basal segment (S9), right posterior basal segment (S10), and left posterior basal segment (S10). At the first operation, the S9 fistula was directly sutured; however, the right S10 fistula could not be closed because the surrounding tissue was fragile. The left lung fistula was deep and crater-shaped; it was closed with the suturing of a plugged free muscle flap. At the second operation, the right S10 fistula was closed with the superimposition of a pedicled intercostal muscle flap. Conclusion Patients with bilateral empyema tend to be with poor general condition and, therefore, less invasive treatments are required initially. Closure of fistulae is an essential process for the treatment of empyema with fistulae. We could manage the fistulae using several techniques with 2-stage operation. Although the efficacy of using a free intercostal muscle flap to close the fistula has not been adequately verified, it is simple and less invasive and, thus, might be a useful option in cases where the patient is too ill to undergo a more invasive operation or when the surgical approach should be done in a short time